What change in BMI is required to improve cardiovascular outcomes in childhood and adolescent obesity lifestyle interventions: a meta-regression. (11th May 2021) - El-Medany, A; Birch, L; Hunt, LP; Matson, RIB; Chong, AHW; Beynon, R; Hamilton-Shield, J; Perry, R
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This study was supported by the NIHR Biomedical Research Centre at University Hospitals Bristol NHS Foundation Trust and the University of Bristol Background: There is minimal evidence regarding the change of body mass index (BMI) needed to improve cardiovascular health in obese children. This paper aims to establish the minimum change in body mass index standard deviation score (BMI-SDS) needed to improve lipid profile and blood pressure (BP) of obese children and adolescents, to aid future trials and guidelines. Methods: Studies with participants involved in lifestyle interventions, aged 4–19 years, with a diagnosis of obesity according to defined BMI thresholds, were considered for inclusion in a large systematic review. Interventions had to report pre- and post-intervention (or mean change in) BMI-SDS, plus either systolic blood pressure (SBP), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and/or triglycerides (TG). Random effects meta-regression quantified the relationship between mean change in BMI-SDS and mean change in cardiovascular outcomes. Results: Seventy-one papers reported various cardiovascular measurements and mean change in BMI-SDS. Fifty-four, 59, 46, and 54 studies were analysed; reporting change in SBP, HDL, LDL, and TG respectively. Reduction in mean BMI-SDS was significantly related to improvements in SBP, LDL, TG, and HDL (p < 0.05); BMI-SDS reductions of 1, 1.2, and 0.7 ensured a mean reduction of SBP, LDL, and TG respectively although an equivalent value for HDL improvement was indeterminate. Conclusions: Reductions in mean BMI-SDS of >1, >1.2, or >0.7 are likely to reduce SBP, LDL, and TG respectively. Further studies are needed to clarify the optimal duration, intensity, and setting for interventions.  Consistency is required regarding derived BMI values to facilitate future systematic reviews and meta-analyses.